Analisis Keterlaksanaan Asesmen Hasil Belajar Siswa pada Kurikulum Merdeka Belajar - Yulis, Sara; Mutia, Nur Balqis; Husna, Raudatul (Education & Learning, 2025)
This research was conducted at SDN Kabu Aceh Timur to analyze the implementation of student learning assessment, with the background of challenges in providing adequate facilities and infrastructure. The study aims to understand the implementation of assessment and the challenges faced by teachers. The type of research used is descriptive qualitative. The result show that in the Merdeka Curriculum, the student learning evaluation includes both academic and character assessments. Formative assessments are used TP track student progress, while summative assessment evaluate the achievement of learning goals. This evaluating also integrates character values through Pancasila-based projects. However, teacher face challenges in implementing the learning assessment, such as limited facilities, difficulties in mastering the curriculum, and applying project-based evaluations, nevertheless, the school strives to improve facilities and provide training for educators to address these obstacles.